3M completes acquisition of Polypore's Separations Media business. Issue 10 (October 2015) - Unknown
Abstract : 3M Co has completed its acquisition of the assets and liabilities associated with Polypore's Separations Media segment from Polypore International Inc, for a purchase price of $1.0 billion.